Legal Protection for Transfer Company Employees after Law Number 11 Year 2020: Perlindungan Hukum Bagi Karyawan Perusahaan Alihdaya Pasca Disahkannya Undang-Undang Nomer 11 Tahun 2020 - Asnawi, Minan Zuhri; Phahlevy, Rifqi Ridlo (Indonesian Journal of Law and Economics Review, 2021)
Legal protection includes a series of legal actions that must be taken by law enforcement officers to ensure a sense of security, both mental and physical, from interference and threats from outside. To answer the problems above, the researcher uses normative research methods. The approach method used in this research is to assess the legal relationship between outsourced workers and employers based on Law no. 13 of 2003 and its implementing regulations. Researchers take a normative legal approach. The rules of Law 13 of 2003 as amended by Law 11 of 2020, regarding the employment relationship between outsourcing entrepreneurs and workers are not limited, as long as it is stated in the PKWT and PKWTT agreements. Article 61 a between articles 61 and 62 If the PKWT is terminated, the employer is obliged to provide compensation to the workers. This compensation is equivalent to severance pay for permanent employees if there is a concept that the company is obliged to pay compensation to its employees; however, this is a new provision that was not regulated in the previous Manpower Act.